2017
DOI: 10.1557/mrc.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a hexagonal closed-packed phase in Al0.5CoCrFeNi high entropy alloy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Besides promising properties of HEAs caused by their multiphase microstructure, the most important parameter for their potential applications is their thermal stability. It has been found that the phase evolution during heat treatment largely depends on such factors as alloy composition, concentration of the elements, and synthesis route [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Besides promising properties of HEAs caused by their multiphase microstructure, the most important parameter for their potential applications is their thermal stability. It has been found that the phase evolution during heat treatment largely depends on such factors as alloy composition, concentration of the elements, and synthesis route [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for a long time high entropy alloys have been believed to form primarily bcc and/or fcc phases. The hcp phase has only been recently observed in CoCrFeMnNi [33], AlHfScTiZr [34], Al 0.5 CoCrFeNi [35] and CoCrFeNi [36]. Here we study derivatives of the CoCrFeMnNi system where the hcp and fcc phases co-exist.…”
Section: Background and Motivationmentioning
confidence: 93%
“…Grain coarsening occurred after heat treatment at 850°C, and the fine bcc phase emerged and distributed uniformly in the matrix, as seen in Figure 1 ( Wang et al, 2017a). Another study reported the precipitation of a plate-like hexagonal closed-packed phase with high cobalt content located at the interdendritic region of the Al 0.5 CoCrFeNi HEA after 650°C/8 h heat-treatment (Wang et al, 2017b). Though a simple shear, the bcc phase could transform into the hcp phase, and the crystal orientation relationship between these two phases has also been to been established as [11][12][13][14][15][16][17][18][19][20] hcp || [111] bcc (000-1) hcp || (10-1) bcc .…”
Section: Thermodynamic Ways Of Annealingmentioning
confidence: 94%